Sejarah Rumah Tradisional Umah Pitu Ruang di Tanah Gayo, Aceh - Sufandi Iswanto; Ramazan Ramazan; Nina Suryana (Jurnal Pendidikan dan Kebudayaan, 2022)
This research discusses about umah pitu ruang found in the Gayo community in Tanah Gayo, Aceh. The purpose of the study is to describe the meaning umah pitu ruang and the history of the emergence of umah pitu ruang in the Gayo community. This study uses the historical method using five stages, namely topic selection, heuristics, verification, interpretation, and historiography. The results showed that umah pitu ruang is a series of words from the Gayo language, umah means house, pitu means seven, and space means space. Thus, umah pitu ruang can be interpreted as a house with seven rooms. The term umah itself is the influence of Austronesian traditions and languages. Umah pitu ruang is thought to have appeared hundreds of years ago long before the emergence of the Linge Kingdom. It all started with the arrival of the ancestors of the Gayo tribe who initially lived in baking pans but later built simple stilt houses. Over time, the number of residents, cultural, and customary knowledge that developed led to the emergence of umah pitu ruang.